La gouvernance urbaine « les pieds dans l’eau » - Thibault Boughedada (Revue Internationale des Études du Développement)
This paper analyzes the interactions between land development policies in Cotonou (Benin) – in particular so-called subdivision and land consolidation operations – and the city’s significant exposure to environmental constraints, in particular flooding. It is based on fieldwork that covers several vulnerable city neighborhoods, and relies on qualitative interviews with a whole chain of actors involved at different levels, from the offices of surveyors and town planners to the various municipal and ministerial services dealing with land and land development policies. This work shows that these policies reinforce rather than reduce the vulnerability of the city and its inhabitants to environmental risks.